1983
DOI: 10.1159/000241620
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GABA and Some GABA Analogues on Respiratory Regulation in the Preterm Rabbit

Abstract: Preterm neonatal rabbits (gestational age 29 days) were given GABA (750 mg/kg) or the GABA-like drugs muscimol (2 mg/kg) and GHBA (375 mg/kg) intraperitoneally. Basal respiration and the ventilatory response to 10% CO2 were studied, before and after drug administration, in a whole body plethysmograph during halothane anesthesia. The three drugs tested all caused a decrease in minute volume. The decrease in minute volume was mainly due to a decrease in tidal volume after GABA and muscimol, while GHBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

1984
1984
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
1
5
1
Order By: Relevance
“…Our results are in agreement with those of a study on chloride hydrate sedated piglets during the 1st week of postnatal life in which bicuculline had no respiratory effects [14]. However, they are contrary to the GABAevoked decrease in V T in anesthetized preterm rabbits [11] and the bicuculline-evoked increase in phrenic nerve activity in anesthetized kittens 1 day of age [26].…”
Section: Ventilatory Effects Of Aoaasupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are in agreement with those of a study on chloride hydrate sedated piglets during the 1st week of postnatal life in which bicuculline had no respiratory effects [14]. However, they are contrary to the GABAevoked decrease in V T in anesthetized preterm rabbits [11] and the bicuculline-evoked increase in phrenic nerve activity in anesthetized kittens 1 day of age [26].…”
Section: Ventilatory Effects Of Aoaasupporting
confidence: 91%
“…Consistent with the presence of tonic GABA A receptor mediated inhibition of inspiratory neurons, bicuculline, a GABA A receptor antagonist, increases inspiratory activity [9] and the rate of breathing [7] in anesthetized adult cats and rabbits. In anesthetized preterm rabbits, newborn kittens and opossums, and in a neonatal rat brainstem-spinal cord preparation in vitro, respiratory effects of GABA and bicuculline resemble those in adult animals [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have attempted to elucidate the mechanisms responsible for the ventilatory depression that is seen after a few minutes of hypoxia in the neonate (2)(3)(4)(5)(7)(8)(9)(10)(11)(12)(13)(14). Some investigators have suggested that the ventilatory depression during sustained hypoxia could be due to a relative alkalosis of the brain stem structures produced by a washout of carbon dioxide that result from the increase in brain blood flow that occurs during hypoxia (1 5, 20).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism responsible for this biphasic response to hypoxia has not been completely elucidated. Various neurotransmitters or modulators released during hypoxia such as endorphins, y-aminobutyric acid, prostaglandins, and adenosine have been suggested as possible mediators of the late decrease in ventilation (2,(7)(8)(9)(10). Other possible explanations have included changes in lung mechanics, a decrease in the metabolic rate, respiratory muscle fatigue, and inhibition of peripheral chemoreceptors (3, 1 1 -14).…”
mentioning
confidence: 99%
“…which may be a respiratory inhibitor (1 1-16). Branched-chain AA may also compete with glutamate for decarboxylation, resulting in increased glutamate levels and consequently reducing the production of GABA, which is a n important respiratory depressant (17)(18)(19). Because a late ventilatory depression occurs in neonates during hypoxia (20)(21)(22)(23) and because this depression may in part be caused by an increase in inhibitory neurotransmitters, counterbalancing their effect by dietary intervention could reverse the ventilatory depression.…”
Section: Divisiorl O F R'c~ot~atolo~~~ Dcpurtrnolt ~Fmentioning
confidence: 99%